1998
DOI: 10.1128/aac.42.8.1996
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Activity and Pharmacokinetic Evaluation of a Novel Long-Acting Carbapenem Antibiotic, MK-826 (L-749,345)

Abstract: MK-826 (formerly L-749,345), is a potent 1-β-methyl carbapenem with a long half-life and broad spectrum of activity. This compound is presently in phase-II clinical trials. Its activity against a number of gram-positive and gram-negative organisms was compared to those of imipenem (IPM) and eight other β-lactam agents in two in vivo murine infection models. The distribution in tissue and pharmacokinetic properties of MK-826 and ceftriaxone (CTRX) were also evaluated in CD-1 mice following a single intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…However, it is less potent against gram-positive organisms, Acinetobacter sp and P. aeruginosa, than imipenem or meropenem. [46][47][48] Faropenem, a new oral carbapenem with twicedaily dosing, was studied in vitro against both gram-positive and gram-negative pathogens, including ESBL isolates. In vitro data suggest that it is less active than imipenem against P. aeruginosa.…”
Section: Treatmentmentioning
confidence: 99%
“…However, it is less potent against gram-positive organisms, Acinetobacter sp and P. aeruginosa, than imipenem or meropenem. [46][47][48] Faropenem, a new oral carbapenem with twicedaily dosing, was studied in vitro against both gram-positive and gram-negative pathogens, including ESBL isolates. In vitro data suggest that it is less active than imipenem against P. aeruginosa.…”
Section: Treatmentmentioning
confidence: 99%
“…Ertapenem is a newer ␤-lactam antibacterial agent which covers various infections by gram-positive and -negative aerobes and anaerobes [1]. It has been approved for intra-abdominal and acute gynaecological infections, as well as communityacquired pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…This dosage best simulated ertapenem pharmacokinetics in humans for their model. Since the elimination half-life of ertapenem is expected to increase at least two-to three-fold in the setting of renal impairment induced by uranyl nitrate [7,24,25], our dosage of 200 mg/kg q6h is not excessive. Furthermore, both studies demonstrated that even doses without evident bactericidal activity reduced mortality in neutropenic mice.…”
Section: Discussionmentioning
confidence: 99%